2002
DOI: 10.1192/bjp.181.3.208
|View full text |Cite
|
Sign up to set email alerts
|

Duration of major depressive episodes in the general population: Results from the Netherlands Mental Health Survey and Incidence Study (NEMESIS)

Abstract: Although half of those affected with MDE recovered rapidly, the risk of chronicity (duration 24 months or more) was considerable. This underlines the necessity of diagnosing and treating those at risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

31
317
0
15

Year Published

2004
2004
2018
2018

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 422 publications
(363 citation statements)
references
References 18 publications
31
317
0
15
Order By: Relevance
“…Clinicians were also explicitly asked to screen their caseload for potentially eligible participants. A depressive episode was defined as “chronic” if symptoms persisted for ≥12 months, because research has shown that chances of recovery decrease substantially after this period (Spijker et al., 2002). Inclusion criteria were (a) age ≥ 18, (b) current depressive episode according to DSM‐IV criteria with a duration of ≥12 months, (c) moderate to high levels of depressive symptoms (Inventory of Depressive Symptomatology‐Self‐Report [IDS‐SR] ≥ 21), (d) at least one adequate trial of antidepressant medication during the current episode (defined as appropriate doses of antidepressant medication for ≥4 weeks or patient's refusal to use medication contrary to the advice of a psychiatrist), and (e) previous psychological treatment during the current episode (defined as ≥10 sessions of CBT or IPT or < 10 sessions if discontinued because of patient's withdrawal).…”
Section: Methodsmentioning
confidence: 99%
“…Clinicians were also explicitly asked to screen their caseload for potentially eligible participants. A depressive episode was defined as “chronic” if symptoms persisted for ≥12 months, because research has shown that chances of recovery decrease substantially after this period (Spijker et al., 2002). Inclusion criteria were (a) age ≥ 18, (b) current depressive episode according to DSM‐IV criteria with a duration of ≥12 months, (c) moderate to high levels of depressive symptoms (Inventory of Depressive Symptomatology‐Self‐Report [IDS‐SR] ≥ 21), (d) at least one adequate trial of antidepressant medication during the current episode (defined as appropriate doses of antidepressant medication for ≥4 weeks or patient's refusal to use medication contrary to the advice of a psychiatrist), and (e) previous psychological treatment during the current episode (defined as ≥10 sessions of CBT or IPT or < 10 sessions if discontinued because of patient's withdrawal).…”
Section: Methodsmentioning
confidence: 99%
“…months (Spijker et al, 2002). As well as a high prevalence in women, duration is often longer for females than for males (Ayuso-Mateos et al, 2001;Bebbington et al, 1998;Üstün et al, 2004).…”
Section: Accepted M Manuscriptmentioning
confidence: 99%
“…We can also examine the extent to which well-being is affected by gender, health status, age and the presence of children. Many studies have found that socio-demographic factors play an important role in explaining inter-individual variability in well-being 14,15,16 and depressive symptoms 17,18 , as well as in physical morbidity 19,20,21,22 .…”
Section: Socio-demographic Factors and Labour Market Characteristicsmentioning
confidence: 99%